Anticoagulants: The Need for Austere Monitoring: Utilization and Evaluation Pattern from Tertiary Care Referral Hospital, Kerala - Korangal, Shafeera; Chandrashekar, Dilip; Joseph, Christy Mary (Journal of Pharmacy Practice and Community Medicine)
Background: Drug utilization evaluation is a systematic quality improvement process that is designed to assess the rational use of medicines in the populations. This study is designed to analyze the utilization pattern of anticoagulants in a tertiary care hospital. Aim: The objective of the study is to assess the utilization and prescribing patterns of anticoagulants in various departments of the hospital. Methods: A prospective observational study was conducted for 4 months from 1st September 2019 to 31st December 2019 to evaluate the utilization of anticoagulants among the 75 patients selected from 3 departments (cardiology, neurology and general medicine) and their respective intensive care units of a tertiary care referral hospital. Results: During the study period, among the anticoagulants prescribed, injection enoxaparin was most the commonly prescribed followed by injection heparin in the cardiology and neurology departments. Oral anticoagulants were prescribed in small number of patients and the most commonly administered drugs were warfarin and acenocoumarol. From the 75 cases analyzed, the monitoring parameters Prothrombin Time (PT), International Normalized Ratio (INR), APTT were monitored in 50 cases and were not analyzed in 25 cases. Target INR was achieved in 45 patients. The remaining 5 cases showed abnormal values in whom the drug therapy was withheld. Conclusion: Anticoagulants are the class of drug that are most commonly prescribed in the hospitals and should follow appropriate guidelines to ensure the rational use of drugs. Injection enoxaparin was preferred over other anticoagulants in all the selected departments. The pattern of potential drug-drug interactions with enoxaparin was found to be moderate and mild. Medication errors, mostly prescription-centered, were reported. Monitoring parameters for anticoagulant therapy has to be evaluated as per the ACCP guidelines (revised 2016), in order to ensure the rational use of drug but was performed only in some patients. Maintenance of normal INR level through the evaluation of monitoring parameters is thereby inevitable.
Keywords: APTT; Anticoagulants; Enoxaparin; INR; PT.